Advantages and Disadvantages of Language Capability Students and Alumni of Modern Islamic Boarding Schools in Indonesia - Ayat Nuraini; Farah Hasballah; Ade Novit Syahputra (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
So far, Islamic boarding schools have been identical with their students who are good at religion as well as Arabic, but the fact is, there are many boarding school graduates who are good at speaking Arabic but can’t speak correctly with Arabic grammar, and then there are others who understand Arabic grammar (qawaid) correctly but can’t speak the Arabic language. This study aims to identify and analyze the language skills of modern Islamic boarding school students. Using field research conducted by interviewing various alumni of modern Islamic boarding schools in Indonesia, this research contributes to Arabic language educators so that they can understand what causes the many alumni of modern Islamic boarding schools to be proficient in speaking but weak in Arabic grammar. The results of this study show that the modern Islamic boarding school education system is more open and requires students to speak in foreign languages, namely Arabic and English, without burdening students to use good and correct Arabic grammar when speaking and learning Arabic , and without studying classical books such as a salaf pesantren that studies and explores the rules of Arabic grammar and the meaning of the book's contents. This research is in the form of criticism and suggestions so that modern Islamic boarding school education can further improve the abilities of its students.